Effects of different pollinizer cultivars and pollination times on the fruit set and quality of pitaya cv. ‘Bloody Mary’ (Hylocereus polyrhizus) - DEMIRKAPLAN, GIZEM; GUBBUK, HAMIDE; BALKIC, RECEP (The Indian Journal of Agricultural Sciences, 2025)
Pitaya (Hylocereus polyrhizus Britton and Rose) is a valuable crop due to its growing global demand, unique flavour, nutritional benefits, and potential for commercial production. An adaptation study of the ’Bloody Mary’ pitaya cultivar conducted in subtropical regions confirmed its high adaptability. However, as a sterile cultivar, it requires cross-pollination for optimal fruit set and quality. The study was carried out during 2019 and 2020 at Akdeniz University, Antalya, Turkey to identify the most effective pollinizer cultivars and optimal pollination times for the ’Bloody Mary’ cultivar of pitaya. The pollinizer cultivars evaluated were ’Cosmic Charlie’, ’Red Jaina’, and ’White Jaina’, with pollination carried out at three times, 22:00 hrs, 24:00 hrs, and 06:00 hrs. Data on fruit set and key quality parameters were evaluated. The results showed that both fruit set rate and quality characteristics varied depending on the pollinizer cultivars and pollination times. Fruit peel chroma (C*) and fresh chroma (C*) were significantly affected by the pollinizer cultivars, while the fruit peel hue angle (h°) remained unaffected. ’Red Jaina’ and ’White Jaina’ were the most effective pollinizer cultivars for ’Bloody Mary’, with optimal pollination times for fruit set at 22:00 h and 24:00 h. However, pollination times did not influence several quality parameters.